2002
DOI: 10.1046/j.1365-2044.2002.02273.x
|View full text |Cite
|
Sign up to set email alerts
|

Removal of obstructing blood clot from the lower airway: an alternative suction technique

Abstract: SummaryClotted blood or organised thrombus in the lower airway may present clinicians with life-threatening airway obstruction or pulmonary collapse. An alternative suction technique is described, which applies suction directly to a tracheal tube.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 9 publications
0
14
0
1
Order By: Relevance
“…Furthermore this technique requires the expertise of specialists. Recently, alternative methods for removing endobronchial blood clots have been introduced, such as a Fogarty arterial embolectomy catheter or application of thrombolytics via a flexible bronchoscopy8,9. These methods are only recommended when severe respiratory compromise is present and other alternatives have failed.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore this technique requires the expertise of specialists. Recently, alternative methods for removing endobronchial blood clots have been introduced, such as a Fogarty arterial embolectomy catheter or application of thrombolytics via a flexible bronchoscopy8,9. These methods are only recommended when severe respiratory compromise is present and other alternatives have failed.…”
Section: Discussionmentioning
confidence: 99%
“…These catheters often prove ineffective in removing large clots as the clots do not pass through the catheter and the catheter system cannot develop enough negative pressure [5]. Bodenham described an alternative technique in which negative pressure is directly applied to the tracheal tube using a Y-connector [6]. To prevent progressive air trapping we decided to reverse muscle relaxation and allow spontaneous breathing to resume.…”
Section: Discussionmentioning
confidence: 99%
“…Other rescue techniques that have been described when dealing with blood clots in the lower airway include the use of fiberoptic and rigid bronchoscopy in combination with lavage, suction devices, forceps, snares or arterial embolectomy catheters [6,8,9]. The use of the topical thrombolytic agents streptokinase and urokinase have also been successful [9,10] but they take some time to be effective.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports have demonstrated that an endotracheal tube (ETT) could function as a suction device to clear the airway. 1,2 However, additional equipment is needed to connect the ETT to a suction source, and it may not be immediately available in the operating room. We herein describe a modified suction technique that allows expeditious clearance of regurgitated vomitus during tracheal intubation.…”
Section: To the Editormentioning
confidence: 99%